COMPACT MIMO SLOT ANTENNA OF DUAL-BANDS FOR LTE AND 5G APPLICATIONS - N. A. Shairi, A.M. Ibrahim, I.M. Ibrahim (International Journal of Advanced Science and Technology, 2019)
This study investigates the use of two elements of the multi-input multi-output (MIMO) antenna, to study the dual frequencies (3.1-3.55 and 4.4-4.99) GHz, as well as the (3.4-3.6 and 5.1-5.85) GHz, of the LTE and 5G bands respectively, for smartphone applications. With the proposed dimension of 31 × 31 × 0.8 mm3, the small-sized and medium-structured MIMO antenna not only demonstrated a high degree of efficiency and isolation, but also a lower level of an envelope correlation coefficient. These attributes are well suited for the LTE and 5G band applications, which are be introduced to the American and Japanese markets. The inexpensive FR4 substrate fabricated during this study comes with a thickness of 0.8 mm, a dielectric constant of 4.4 and a copper thinness of 0.035. Subsequent to simulation and structuring of the proposed dual antennas, it was observed that the overage demonstrated an isolation level of (-10dB and -19dB) and (-12 and -19) respectively, for the dual bands mentioned above. The use of the proposed MIMO in the LTE and 5G dual bands led to an improvement in efficiency, isolation and envelope correlation coefficient (ECC).